Using Online Lectures to Promote Engagement: Recognising the Self-Directed Learner as Critical for Practical Inquiry - Robin Henrikson (Flexible Learning Association of New Zealand, 2020)
This study analyzed the relationships between teaching presence, social presence and cognitive presence in online learning environments (Garrison, Anderson, & Archer, 2000), with an emphasis on examining ways in which the design of instructor presentation formats relates to student responses within discussion forums. Both quantitative and qualitative analyses were used to determine the nature of student responses, primarily through the lens of the Practical Inquiry Model (Garrison, 2007) by coding all text within the initial student responses to content-based questions. Twenty students were randomly assigned to two sections in a graduate level, teacher education course. One group was provided metacognitive prompts throughout the asynchronous lecture presentation and told to pause the presentation and document their thinking relative to the prompts. The other group was not asked to pause and write during the presentation nor were there any metacognitive prompts embedded within the presentation. A Pearson's Chi-Square analysis was used to analyze the coding of the text and a form of text analytics was used to seek out the nature of student learning and cognitive presence. There were no significant associations found between the design of the instructor presentation and levels within the Practical Inquiry Model. Furthermore, the themes, number of total themes and word count also remained consistent between the two groups.